2015
DOI: 10.1007/s12011-015-0487-0
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide Exposure Induces Heat Shock Protein Responses in Cock Livers

Abstract: Arsenic is a trace element widely found in nature, and there are several forms of arsenic, including the most toxic form of trivalent arsenic. Arsenic trioxide (As2O3) is widespread in nature and tends to accumulate in animals and humans, thus causing great harm. Although the important role of heat shock proteins (HSPs) has been demonstrated in many types of mammals exposed to As2O3, the function of these proteins in poultry, especially in cocks, remains unclear. In this study, we used experimental animals (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As one of the major inducible HSPs, HSP70 is widely used as a heat stress marker in various studies (Morimoto 1993). Heat exposure can upregulate HSP70 in embryos (Skjaerven et al 2011;Sakatani et al 2012) and increase HSP27 in mammary gland (Li et al 2019), liver (Zhang et al 2016), and cardiac cells (Parida et al 2019). Similarly, our current study found that HSP70 was increased in both abdominal fat and liver and HSP27 was increased in the liver, indicating the adaptive response of these piglets in response to heat stress even when they were in utero of sows and during lactation period.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the major inducible HSPs, HSP70 is widely used as a heat stress marker in various studies (Morimoto 1993). Heat exposure can upregulate HSP70 in embryos (Skjaerven et al 2011;Sakatani et al 2012) and increase HSP27 in mammary gland (Li et al 2019), liver (Zhang et al 2016), and cardiac cells (Parida et al 2019). Similarly, our current study found that HSP70 was increased in both abdominal fat and liver and HSP27 was increased in the liver, indicating the adaptive response of these piglets in response to heat stress even when they were in utero of sows and during lactation period.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular chaperones are a group of proteins that have functional similarity and modulate the proteostasis network by sensing and proofreading misfolded peptides to avoid aggregation [ 184 ]. It has been suggested that exposure to arsenic leads to the disruption of the functions of molecular chaperones [ 185 ]. As a division of the cellular stress response, inorganic arsenic (As 3+ ) was found to induce HSP70 and small HSP’s expression.…”
Section: Toxicological Pathwaysmentioning
confidence: 99%
“…As part of the cellular stress response, iAs 3+ was found to induce the expression of chaperone proteins, especially heat shock proteins HSP70 and sHSPs. Additionally, chronic arsenite exposure was shown to up-regulate heat shock proteins via activation of DAF-16/FOXO transcription factor through oxidative stress …”
Section: Arsenic-induced Disruption Of Proteostasis Networkmentioning
confidence: 99%